Romanticizing Bad Guys: A Psychological Analysis of Ryle in Colleen Hoover's It Ends with Us - Shamam Ismail Otaiwi; Aliaa Abed Mohsen; Marwan Khaleel Yousif (Zanco Journal of Humanity Sciences)
Colleen Hoover’s It Ends with Us became a New York Times bestseller due to its sensitive topic. Most of the available literature explores domestic violence in the novel, with some articles focusing on the character of the protagonist Lily. However, there are no studies on Ryle, the abuser who despite his toxicity was oddly romanticized by many readers. Therefore, this paper addresses this gap by examining the appeal of Ryle’s character. Drawing insights from Richard Keen, Monica L. McCoy, and Elizabeth Powell's study Rooting for the Bad Guy: Psychological Perspective (2012) as it offers useful observations into analyzing the reasons behind the attraction towards bad guys like Ryle. It has been concluded that Hoover’s characterization method leads readers to romanticize Ryle. That is due to many factors such as fundamental attribution error, mere exposure affect, schemas, and fulfilling hidden aggressive tendencies which make readers externalize Ryle’s bad behavior.